Analysis of Industrial Hemp Quality Indicators, a Line for Its Processing and Hemp Short - E. V. Novikov; I. N. Altukhova; N. V. Basova (Сельскохозяйственные машины и технологии, 2020)
It is important to create foreign units alternative, introducing modern domestic technologies and lines in the framework of import substitution for the primary processing of strategic raw materials in the industrial hemp form.(Research purpose) To substantiate the technological scheme of the line for processing industrial hemp into the hemp short, the characteristics of raw materials and low-cost fibers for the primary processing of industrial hemp in the form of tangled mass of incomplete length stems, harvested by a specialized combine.(Materials and methods) Hemp rolls of spring harvesting were processed according to two options: single and double way of raw materials through the line, after which the hemp short quality indicators were determined.(Results and discussion) The authors found out that hemp raw material had broken and tangled stems 36-470 millimeters long, of high separability, with a fiber content of 26-30 percent, but with a small breaking load of 13-17 kilogram-forces. They determined that the fiber yield with a single way was 28-29 percent, with a double way – 23-22 percent. It was shown that a double pass reduced the mass fraction of shives by 3-4 percent in absolute terms and reduced the breaking load by no more than 2 kilogram-force. A low content of defects was revealed: the mass fraction of shives was no more than 7.1 percent, the absence of a “paw”. However, due to the minimum breaking load of the fiber, hemp was assigned to the lower grade.(Conclusions) The authors substantiated the scheme of small-sized and low-cost domestic line for the industrial hemp primary processing. They determined the quality indicators values of the hemp short and its output under various conditions of primary processing. The influence share of the second way through the line on the quality indicators was calculated: fiber yield – 97.3 percent; the breaking load of the twisted ribbon is 42.4 percent; mass fraction of shives – 75.3 percent; the average mass length is 61.2 percent; the weighted average linear density is 99.1 percent.